2009
DOI: 10.1007/s11467-009-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

On torsion-free vacuum solutions of the model of de Sitter gauge theory of gravity (II)

Abstract: It is shown that all torsion-free vacuum solutions of the model of de Sitter (dS) gauge theory of gravity are the vacuum solutions of Einstein field equations with the same positive cosmological constant. Furthermore, for the gravitational theories with more general quadratic gravitational Lagrangian (F 2 + T 2 ), the torsion-free vacuum solutions are also the vacuum solutions of Einstein field equations.Keywords torsion-free vacuum solutions, model of de sitter gauge theory, gravity PACS numbers 04.20.Jb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Actually it has been shown [9,10] that the model with a small cosmological constant may explain the accelerating expansion of the universe and supply a natural transit from decelerating expansion to accelerating expansion without the help of introducing matter fields in addition to dust. It has also been shown [11,12] that all torsion-free vacuum solutions of this model are the vacuum solutions of Einstein's field equation with the same cosmological constant, and vise versa. Therefore, one may expect that the model with a small cosmological constant may pass all solar-system-scale experimental tests for general relativity (GR).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Actually it has been shown [9,10] that the model with a small cosmological constant may explain the accelerating expansion of the universe and supply a natural transit from decelerating expansion to accelerating expansion without the help of introducing matter fields in addition to dust. It has also been shown [11,12] that all torsion-free vacuum solutions of this model are the vacuum solutions of Einstein's field equation with the same cosmological constant, and vise versa. Therefore, one may expect that the model with a small cosmological constant may pass all solar-system-scale experimental tests for general relativity (GR).…”
Section: Introductionmentioning
confidence: 75%
“…In the torsion-free case, the scalar curvature would be a constant from Eq. (12), and, therefore, Σ = const from Eq. (10).…”
Section: A Model Of Ds Gravitymentioning
confidence: 99%
“…where C abcd is the Weyl curvature tensor. It has been shown that all the torsion-free vacuum solutions of the dS gravity model are the vacuum solutions of GR with the same cosmological constant, and vice versa [18,19].…”
Section: Example 1: a Model Of De Sitter Gauge Theory Of Gravitymentioning
confidence: 99%
“…In this viewpoint, the metric field of the base spacetime contains not only the zeroth-order term but also the higher-order terms, as was shown in Eq. (9).…”
Section: Case Amentioning
confidence: 99%
“…The model under this case, hereafter referred to as the dS gravity model or simply as the model, might be very different from GR. But fortunately, it has been shown [8,9] that all torsion-free vacuum solutions of the model are the vacuum solutions of GR with the same cosmological constant, and vise versa. Moreover, it has been shown [10,11] that the model may explain the accelerating expansion of the universe and supply a natural transit from decelerating expansion to accelerating expansion without the help of dark energy.…”
Section: Introductionmentioning
confidence: 99%